2010
DOI: 10.1007/s10562-010-0351-y
|View full text |Cite
|
Sign up to set email alerts
|

Acyclic Amino Acids Catalyzed Direct Asymmetric Aldol Reactions in Aqueous Media Assisted by 2,4-Dinitrophenol

Abstract: The catalytic capabilities of acyclic amino acids for the direct asymmetric aldol reactions assisted by 2,4-dinitrophenol in aqueous media were investigated. Several acyclic amino acids catalyzed asymmetric aldol reactions with excellent stereoselectivity, and afforded the corresponding b-hydroxy ketones in high yields and up to 99% ee. Our result suggested that the L-isoleucine was the most effective one.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…As seen from Table 2 (entries 3 and 4), peptide 3 is less active compared to 4 (ee = 89% and 94%, respectively). The scope and limitations of the direct aldol reaction of cyclohexanone with various aromatic aldehydes, catalyzed by tripeptides, were explored next ( Table 2, entries [5][6][7][8][9][10][11][12]. Benzaldehydes substituted by p-nitro, o-chloro, and o-nitro afforded the corresponding anti-aldol products with high yield and excellent stereoselectivity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As seen from Table 2 (entries 3 and 4), peptide 3 is less active compared to 4 (ee = 89% and 94%, respectively). The scope and limitations of the direct aldol reaction of cyclohexanone with various aromatic aldehydes, catalyzed by tripeptides, were explored next ( Table 2, entries [5][6][7][8][9][10][11][12]. Benzaldehydes substituted by p-nitro, o-chloro, and o-nitro afforded the corresponding anti-aldol products with high yield and excellent stereoselectivity.…”
Section: Resultsmentioning
confidence: 99%
“…The development of metal‐free asymmetric organocatalysts has emerged as an attractive field in organic chemistry to produce enantio‐ and diastereoselectivity products in the past few decades . Either secondary or primary amino acids have proven to be useful organocatalyst for direct aldol reactions . In recent years, L ‐proline and derivatives have been frequently developed for aldol and many other reactions .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic study of the 20 proteinogenic amino acids in the aldol reaction between cyclohexanone and 4‐nitrobenzaldehyde in DMSO and in aqueous DMSO was performed by Hayashi et al A positive water effect on the diastereoselectivity was observed for most amino acids, while the enantioselectivity was increased only when proline, serine, or histidine were used . In pure water, tryptophan appears to be the best catalyst, although in the presence of 2,4‐dinitrophenol isoleucine was the most effective one . Interestingly enough, both in aqueous micelles and in ionic liquids arginine showed a high catalytic efficiency, even if in the first case the enantiomeric excesses of the aldol products were rather low.…”
mentioning
confidence: 97%
“…21 In pure water, tryptophan appears to be the best catalyst, 22 although in the presence of 2,4-dinitrophenol isoleucine was the most effective one. 23 Interestingly enough, both in aqueous micelles 24 and in ionic liquids 25 arginine showed a high catalytic efficiency, even if in the first case the enantiomeric excesses of the aldol products were rather low.…”
mentioning
confidence: 99%